The Used of Taboo Words in Central Cee’s Song Lyrics: Pragmatics Analysis - Abdi Fauzan; Siti Aisyah; Lailatul Musyarofah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examined the use of taboo words in hip-hop lyrics as a means of artistic expression and cultural identity formation, focusing on Central Cee's work as presented in a freestyle. Using a qualitative descriptive method, this study aimed to identify the types, textual locations, and functions of taboo words in song lyrics. Data were collected through documentation and content analysis techniques and then were classified based on pragmatic function. The results showed that the most dominant category was insults and derogatory terms such as “bitches” and “hoes.” In addition, taboo language also acted as a linguistic marker through the use of non-standard terms.